AUTOCORRELAÇÃO TEMPORAL DO INCREMENTO EM DIÂMETRO E AS DIFERENÇAS DE CRESCIMENTO ENTRE GRUPOS DE ESPÉCIES EM UMA FLORESTA OMBRÓFILA DENSA - VATRAZ, Silvane; ALDER, Denis; SILVA, José Natalino Macedo (Brazilian Journal of Biometrics, 2018)
The objective of this study was to verify the existence of temporal autocorrelation between two consecutive measurements of diameter increment (1984-1994 and 1994-2004) and to identify patterns of diameter growth rates between different functional groups of species. The study was undertaken in the forest management area of Jari Forest S.A., Vitória do Jari – AP, Brazil. Three permanent plots were used of one hectare each (100 × 100 m), on which were measured all trees with DBH ≥ 20.0 cm. Pearson correlation was used to verify the existence of autocorrelation of growth, by diameter classes and functional groups. The grouping of species was based on building a two-axis graph relating the average diameter increment and the 95% percentile of the diameter distribution. Analysis of variance (α = 0.01) and the Tukey test (α = 0.05) were used to check for differences between increments. The result of this analysis detected the temporal autocorrelation of growth and different growth patterns among some diametric classes. Grouping species was found to be a useful tool for identifying functional groups and the analysis indicated that there are growth differences among some groups.